Molecular Analyses of Left‐ and Right‐Sided Tumors in Adolescents and Young Adults with Colorectal Cancer. (17th December 2019) - Salem, Mohamed E.; Battaglin, Francesca; Goldberg, Richard M.; Puccini, Alberto; Shields, Anthony F.; Arguello, David; Korn, W. Michael; Marshall, John L.; Grothey, Axel; Lenz, Heinz‐Josef
Abstract: Background: The incidence of colorectal cancer (CRC), particularly left‐sided tumors (LT), in adolescents and young adults (AYA) is rising. Epigenetic events appear to play an important role in tumorigenesis and cancer progression, especially in younger patients. We compared molecular features of LT to right‐sided tumors (RT) in AYA. Materials and Methods: A total of 246 LT and 56 RT were identified in a cohort of 612 AYA with primary CRC. Tumors were examined by next‐generation sequencing (NGS), protein expression, and gene amplification. Tumor mutational burden (TMB) and microsatellite instability (MSI) were determined based on NGS data. Results: RT showed higher mutation rates compared with LT in several genes including BRAF (10.3% vs. 2.8%), KRAS (64.1% vs. 45.5%), PIK3CA (27% vs. 11.2%), and RNF43 (24.2% vs. 2.9%). Notably, additional mutations in distinct genes involved in histone modification and chromatin remodeling, as well as genes associated with DNA repair and cancer‐predisposing syndromes, were characteristic of RT; most frequently KMT2D (27.8% vs. 3.4%), ARID1A (53.3% vs. 21.4%), MSH6 (11.1% vs. 2.3%), MLH1 (10.5% vs. 2.3%), MSH2 (10.5% vs. 1.2%), POLE (5.9% vs. 0.6%), PTEN (10.8% vs. 2.3%), and BRCA1 (5.4% vs. 0.6%). MSI was seen in 20.8% of RT versus 4.8% of LT. RT had a higher frequency of TMB‐high regardless of MSI status. Conclusion: Molecular profiling of AYA CRC revealed different molecular characteristics in RT versus LT. Epigenetic mechanisms and alteration in DNA repair genes warrant further investigation and may be a promising treatment target for CRC in AYA. Implications for Practice: Colorectal cancer (CRC) in adolescents and young adults (AYA) comprises a distinct entity with different clinicopathologic features and prognosis compared with older patients. Molecular profiling of right‐ and left‐sided tumors in AYA is needed to gain novel insight into CRC biology and to tailor targeted treatment in this age group. This study found that right‐ and left‐sided CRC show distinct molecular features in AYA, overall and in subgroups based on microsatellite instability status. Alterations in DNA double‐strand break repair and homologous recombination repair, as well as epigenetic mechanisms, appear to play a critical role. The present molecular profiling data may support the development of personalized treatment strategies in the AYA population. Abstract : This article explores the molecular makeup of left‐sided and right‐sided colorectal cancers in populations aged 40 years.